Surveillance of HCC Patients after Liver RFA: Role of MRI with Hepatospecific Contrast versus Three-Phase CT Scan—Experience of High Volume Oncologic Institute - Vincenza Granata; Mario Petrillo; Roberta Fusco; Sergio Venanzio Setola; Elisabetta de Lutio di Castelguidone; Orlando Catalano; Mauro Piccirillo; Vittorio Albino; Francesco Izzo; Antonella Petrillo (Gastroenterology Research and Practice)
Purpose. To compare the diagnostic accuracy of hepatospecific contrast-enhanced MRI versus triple-phase CT scan after radiofrequency ablation (RFA) in hepatocellular carcinoma (HCC) patients. Methods. Thirty-four consecutive HCC patients (42 hepatic nodules) were treated with percutaneous RFA and underwent MR and CT scans. All patients were enrolled in a research protocol that included CT with iodized contrast medium injection and MR with hepatospecific contrast medium injection. All patients were restaged within four weeks and at 3 months from ablation. The images were reviewed by four different radiologists to evaluate tumor necrosis, residual or recurrence disease, and evidence of new foci. Results. Thirty-two nodules were necrotic after treatment; 10 showed residual disease. Six new HCCs were identified. At first month followup CT has identified 34 necrotic lesions and 8 residual diseases; no new foci were recognized. At MRI instead, 32 complete necrotic lesions were identified, 10 lesions showed residual disease, and 2 new HCCs were found. At three months, CT demonstrated 33 completely necrotic lesions, 9 residual diseases, and 2 new HCCs. MR showed 31 complete necrotic lesions, 11 cases of residual disease, and 6 new HCCs. Conclusions. Hepatospecific contrast-enhanced MRI is more effective than multiphase CT in assessment of HCC treated with RFA.